Our Public Health History in Florida: Interview with Charles S. Mahan - Robert J. McDermott (University of North Florida, 2005)
Charles S. Mahan, MD was the second Dean of the University of South Florida College of Public Health (1995- 2002). A native of West Virginia, he received his MD degree from Northwestern University and did his residency training at the University of Minnesota. He moved to Florida in 1974 to be Professor of Obstetrics and Gynecology and Director of Ambulatory Services for Women at the University of Florida, and Director of the North Central Florida Maternal and Infant Care Program. He directed the Florida Department of Health from 1988 to 1995, the period just prior to becoming Dean of the USF COPH. He is the Past President of the Association of State and Territorial Health Officials (ASTHO). He also has served as the Chair of the Advisory Committee to the Director of the Centers for Disease Control and Prevention. A recipient of numerous recognitions and awards during his career, Dr. Mahan received the prestigious Martha May Elliot Award in 2004 from the American Public Health Association for exceptional career contributions to maternal and child health. Since stepping down as Dean, Dr. Mahan has served as Program Director of Maternal and Child Health Policy for the USF COPH's Lawton and Rhea Chiles Center for Healthy Mothers and Babies. He holds joint appointments in the Department of Community and Family Health and the Department of Obstetrics and Gynecology. This interview was conducted between April 3, 2005 and April 26, 2005.